Teeth complexity, hypsodonty and body mass in Santacrucian (Early Miocene) notoungulates (Mammalia) - Cassini, Guillermo Hernán (2017)
Notoungulates, native South American fossil mammals, have been recently objective of several palaeoecological studies. Ecomorphology and biomechanics of the masticatory apparatus, together with micro and mesowear analyses on tooth enamel, were applied in order to understand their palaeobiology. In particular, the relationship between some dental traits (hypsodonty, occlusal surface area and complexity) and body mass is still poorly understood. These features were measured by means of the hypsodonty index (HI), occlusal surface area (OSA) and tooth area (OTA), enamel crest complexity (ECC) and length (OEL). The relationships between these indices were evaluated in ﬁve pan-contemporaneous Santacrucian Notoungulata genera from Patagonia: Adinotherium andNesodon (Toxodontia), Interatherium, Protypotherium and Hegetotherium (Typotheria). While OSA, OTA and OEL were size dependent and strongly correlated, HI and ECC were size independent. All notoungulates analysed have very hypsodont teeth, indicating high rates of tooth wear in response to an increase of abrasives consumed with the food; their tooth occlusal area and complexity could be related to chewing efforts associated with the toughness of the plants consumed. HI, OSA and ECC were considered useful for paleoecological reconstructions, but the results presented here show that these three features are integrated as a complex, so should not be evaluated separately.